Color and Motif Adjustment Strategies of Batik Cap in Overcoming Consumer Ambiguity for Batik MSME Sales Improvement in Jakarta: Strategi Penyesuaian Warna dan Motif Batik Cap dalam Mengatasi Ambiguitas Konsumen untuk Peningkatan Penjualan UMKM Batik di Jakarta - Ade; Danang Aziz Akbarona; Arif Hidayat (OGZ Research & Publishing, 2026)
Abstract Objective: This study aims to examine color and motif adjustment strategies of batik cap in reducing consumer ambiguity to increase batik MSME sales in Jakarta.Methodology: A descriptive qualitative approach was employed with thematic analysis of 8 informants consisting of 2 batik cap MSME practitioners, 5 multigenerational consumers (ages 22–29 and 58–65), and 1 Visual Communication Design academic. Data were collected through in-depth interviews, field observation, and documentation studies.Findings: The research revealed three dimensions of consumer ambiguity: (1) perceptual ambiguity (inability to distinguish batik cap from digital printing), (2) referential ambiguity (emptiness of symbolic meaning of traditional motifs among younger generations), and (3) evaluative ambiguity (collapse of cultural hierarchy due to inconsistent product positioning). Successful MSMEs implemented three integrated strategies: generation- and region-based segmented visual design, cultural bridging through the principle of